The effects of ethylene on sweetpotato storage - Amoah, Robert Sarpong (Cranfield University, 2014)
Sweetpotato (Ipomoea batatas (L.) Lam.) is an important food security crop in many parts of the developing world. Despite its economic value and growing contribution to nutrition and health in tropical and sub-tropical countries, sweetpotato has a short postharvest life. Inhibition of sprout growth to permit long-term storage and marketing of the roots is a major challenge in the sweetpotato industry. To date, no technically and economically satisfactory method is available to extend the tropical storage of sweetpotato. Previous studies have demonstrated the efficacy of both exogenous ethylene and the ethylene perception inhibitor 1-methylcyclopropene (1-MCP) in suppressing sprout growth in other root crops such as potato and onion, which display differential endodormancy. It has been proposed, through studies by others, that ethylene and 1-MCP may also enhance sweetpotato storage. In the present study, the physiological and biochemical effects of exogenously applied ethylene and 1-MCP were further investigated. Cont/d.